Trade Integration in Latin America : A Network Perspective - Beaton, Kimberly (IMF Working Papers; Working Paper ;, 2017)
The paper applies a network analysis framework to analyze the regional and global integration of Latin American and Caribbean (LAC) countries. We compare network-based measures of trade integration to conventional measures, decomposing integration along several dimensions to better understand the sources of trade connectivity and their impact on growth. The paper finds that LAC countries are relatively well integrated in terms of links to diversified markets, but the strength of those links is weak. Comparing trade integration to predictions from gravity models, we find many LAC countries have significant scope to improve connectivity and increase their roles in regional and world trade networks.